THE EFFICACY OF LASER THERAPY AND IBUPROFEN ON PAIN AFTER ELASTOMERIC SEPARATOR PLACEMENT: RAPID REVIEW - Simarmata, Regina Yosephine; Evangelina, Ida Ayu; Laviana, Avi; Mardiati, Endah (Odonto : Dental Journal, 2021)
Background: Separator placement is the first step in orthodontic treatment, which aims to create space between teeth before molar band placement. This procedure can cause pain for the patient. Pain management after separator placement can be done through pharmacological and non-pharmacological approaches.Method: The aim of this rapid review was to determine the efficacy of laser therapy and ibuprofen for pain management after elastomeric separator placement in orthodontic treatment.Result: Ten articles were included in this review, four articles gave laser therapy interventions and six articles gave ibuprofen therapy interventions. The result of the quality assessment using Strength of Recommendation Taxonomy (SORT) was laser therapy intervention has one good quality articles and three limited-quality articles, while ibuprofen therapy has two good quality articles and four limited-quality articles.Conclusion: The efficacy of laser therapy and the efficacy of ibuprofen on pain after separator placement is good, with the strength of the clinical recommendation of ibuprofen is better than laser therapy.